A CRITICAL TIME FOR BRIDGEBUILDING: CATHOLIC THEOLOGICAL ETHICS TODAY - George Kochuthara, Shaji (Asian Horizons, 2018)
The Third International Conference of Catholic Theological Ethics in the World Church (CTEWC) Sarajevo, Bosnia and Herzegovina, 26-29 July 2018 “We are called to recognize every sign and mobilize all our energy in order to remove the walls of division and to build bridges of fraternity everywhere in the world,” said Pope Francis in a letter addressed to the participants of the international conference of moral theologians held at Sarajevo from 26 to 29 July 2018. The conference, “A Critical Time for Bridge-Building: Catholic Theological Ethics Today,” was the third international conference organized by Catholic Theological Ethics in the World Church (CTEWC). About 500 moral theologians from 78 countries from all the five continents participated in it. The conference focused on the urgent crises facing the international community, namely global ecological crisis, the refugee crisis, and the lack of political leadership to address these issues, and the need of global solidarity to address these issues through building bridges between nations, cultures and religions. The conference, which had about 40 keynote and plenary papers, above 100 concurrent session papers and 120 academic posters was an opportunity not only to critically evaluate the present crisis, but also to try to address the issues through renewed hope and committed action in solidarity.